An Exploratory Search for Potential Molecular Targets Responsive to the Probiotic Lactobacillus salivarius PS2 in Women With Mastitis: Gene Expression Profiling vs. Interindividual Variability - de Andrés, Javier; Jiménez, Esther; Espinosa-Martos, Irene; Rodríguez, Juan Miguel; García-Conesa, María-Teresa (Frontiers in Microbiology, 2018)
Probiotics constitute an attractive alternative in the battle against microbial infections. Oral administration of certain strains of lactobacilli isolated from human milk has resulted in an effective reduction of the bacterial load as well as an improvement of the mastitis-associated symptoms. Nevertheless, little is yet known about the potential molecular mechanisms and specific targets implicated in these effects. Transcriptomic profiling has been used to search for disease-associated and therapy-responsive molecules in different disorders and experimental models. We have applied for the first time a gene expression-based molecular approach to explore for potential targets responsive to intervention with a probiotic in: i) breast milk somatic cells (n=17) and ii) blood leukocytes (n=19). Women with mastitis ingested a new strain of lactobacilli, Lactobacillus salivarius PS2 (3× capsules per day, each capsule contained 9.5 log10 CFU) for 21 days. We applied Affymetrix microarrays and Taqman one-step quantitative reverse transcription PCR (RT-qPCR) to analyze and compare gene expression changes between samples pre- and post-treatment. Our results substantiate the involvement of inflammatory and cell-growth related pathways and genes in the breast milk somatic cells following the intake of L. salivarius PS2. Individual analyses of selected genes: 1) supported the upregulation of STC1 and IL19 and the downregulation of PLAUR and IFNGR1 in the somatic cells of the patients as potential targets responsive to the probiotic, 2) detected a lack of a relationship between the gene expression responses in the two types of cells and 3) evidenced a substantial interindividual variability in the gene expression changes in both types of cells. Our study provides an insight into the essentiality of incorporating the study of tissue-specific interindividual molecular responsivity into future clinical intervention trials to further understand the complexity of human gene expression responses to therapy and the potentiality of selecting appropriate responsive targets.